Pengendalian Kualitas Pengelasan Baja SS400 untuk Ducting pada PT. XYZ dengan Metode SQC - M. Zakki Mubarok; Talifatim Machfuroh (Universitas Islam Raden Rahmat, Malang, 2024)
PT XYZ is a steel welding manufacturing company. One of its of its products is a gas exhaust chimney (ducting) made of low carbon Structural Steel (SS400). In the production process, welding defects are often indicated so that it requires rework due to indicated defects. If a ducting has cracks and leaks, the ducting structure will collapse and gas distribution will leak and not be channeled properly. So the purpose of this study is to identify the types of welding defects and countermeasures using the NDT Penetrant method and the Statistical Quality Control (SQC) method to find the causal factors and percentage of defects. The results showed the presence of porosity, undercut and crack welding defects. The most dominant defect is porosity with a defect area of 825 mm percentage (2.23%), undercut 455 mm (1.23%) and crack 155 mm (0.42%). The results of the control chart analysis on SQC that of the three defects there is no deviation out of the control limits set so that the number of defects is still in control and the company can maintain it.